THE ROLE OF EUPHEMISMS IN POLITICAL DISCOURSE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Euphemisms, or indirect and less offensive substitutes for harsh or sensitive terms, play a crucial role in political discourse. Politicians and governments often employ euphemisms to frame controversial actions more favorably, mitigate negative public reactions, and navigate socially delicate issues. These rhetorical devices soften the perception of events and policies, thereby shaping public understanding and opinion. However, euphemisms also raise ethical concerns because they can obscure reality, manipulate public perception, and undermine democratic transparency. This paper explores the diverse functions of euphemisms in political language, examining how they operate as both a diplomatic tool and a means of potential deception. Examples and scholarly literature are analyzed to highlight the complexities of euphemistic language in political contexts.